Limited Role for Interleukin-18 in the Host Protection Response to Pulmonary Infection with Pseudomonas aeruginosa in Mice - Nakasone, Chikara (American Society for Microbiology, 2004)
We report that clearance of Pseudomonas aeruginosa, accumulation of neutrophils, and synthesis of tumor necrosis factor alpha and macrophage inflammatory protein 2 in the infected lung were not largely different in interleukin-18 (IL-18) knockout or transgenic mice compared with control mice. Our results suggest a limited role for IL-18 in the host defense against P. aeruginosa.